The effect of attentional focus strategies on children performance and their EMG activities in maximum a force production task - Ramin Ashraf; Mohammad Taghi Aghdasi; Mansor Sayyah (Turkish Journal of Kinesiology, 2017)
Research has demonstrated the effectiveness of adopting external focus of attention compared to internal focus of attention in children's motor performance and learning. The purpose of present study was to determine whether the external focus of attention had any effect on efficiency (reduction of EMG activity) of children's motor performance. The participants (twenty 8-10-year-old children) first performed vertical jump task in the control condition, then performed under two conditions in a counterbalanced order: external attentional focus and internal attentional focus. In the control condition, the participants performed vertical jump without giving attentional focus instruction. In the external focus condition, the participant's attention was directed to the rungs of a measurement device, namely, Vertec and in the internal focus condition, their attention was directed to their fingers with which they were to touch the rungs. The participants performed 8 vertical jumps in every three conditions and the heights of their jumps were measured. In addition, EMG activity of various muscles (anterior tibialis, biceps femoris, vastus lateralis, rectus femoris, and gastrocnemius) was measured when participants jumped, using electromyography. Results showed that the external focus of attention led to significantly better performance (higher vertical jump) compared to internal focus and control conditions. Also, in the external focus condition, EMG activity was significantly reduced compared to internal the focus and control condition. This present study suggests that adopting external attentional focus will improve effectiveness and efficiency of children's movement in tasks which require maximum force production.